Replenishment of Plant Varieties Market: Sown Rise (Oryza sativa L.) - О. І. Безручко; Ю. М. Довгий (Plant Varieties Studying and Protection)
There discussed directions of use for the valuable groats crop, namely Rice, growth rates of its production in Ukraine, options and necessity of creation new verities by breeders, that favors not just the improved nutrition of people, but improves their health, too. And also a full description is provided for new varieties of soybean listed in the Sate Register of Plant Varieties Suitable for Dissemination in Ukraine.